Business innovation and development in emerging economies - Trinugroho, Irwan; Lau, Evan (Leiden, The Netherlands : CRC Press/Balkema, 2019)
Business Innovation driven by the advancement of technology has dramatically changed the business landscape over recent years, not only in advanced countries but also in emerging markets. It is expected that business innovation could help achieve economic inclusion, which has been a global initiative over the last decade, creating opportunities for all people to benefit from the economic development. These proceedings provide an outlet for discussing the importance of business innovation, especially in emerging countries in helping to reach inclusive economies. The papers cover the subject areas management, accounting, finance, economics and social sciences.
OCLC-licensed vendor bibliographic record.
Keywords: Industries -- Developing countries; Management -- Developing countries; Economic development -- Developing countries; BUSINESS & ECONOMICS / Industries / General; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Economics / General; POLITICAL SCIENCE / Public Affairs & Administration